Pengaruh Literasi Keuangan Syariah dan Kemudahan Akses Layanan terhadap Minat Masyarakat dalam Menggunakan Produk Keuangan di BMT Bungatan - Millah Hanifiyyah; Achmad Febrianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of Islamic finance in Indonesia highlights the importance of Islamic financial literacy and ease of service access in encouraging public interest in using Islamic financial products. A quantitative approach with a causal associative research design was employed in this research. Data were collected through questionnaires using a Likert scale from 104 respondents selected through purposive sampling. Multiple linear regression analysis with SPSS was applied after conducting classical assumption tests. The findings reveal that partially, Islamic financial literacy does not significantly affect public interest in using Islamic financial products, indicated by a significance value of 0.256 (>0.05). In contrast, ease of service access has a positive and significant effect on public interest, with a significance value of 0.000 (<0.05). Simultaneously, both independent variables influence public interest, although ease of service access emerges as the most dominant factor with a beta coefficient value of 0.694. These findings demonstrate that practical, fast, and easily understood service access plays a more influential role in attracting public interest than the level of Islamic financial literacy.